Concealment of Crime Revealing by Detailed Autopsy: A Study - Verma L.C; Meena S.K; Tatwal B (Institute of Medico-legal Publications Pvt Ltd, 2021)
Ancient literature suggests a link in between modus operandi of different crimes in different parts ofuniverse, but there is a wide variation in motive and execution of crime. However assailants are very keen toconceal crime by different methods. Defacement of body, electrocution , throwing into river, burial , burningthe body , dismembering the body parts and throwing body on railway track are more common methods ofconcealment of crime. Among various method of concealment of crime some of are discussing in this articlewith other related factors.